2018
DOI: 10.1007/s40265-018-1033-0
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Systemic Treatment of Neuroendocrine Tumors: Current Options and Future Perspectives

Abstract: Neuroendocrine tumors (NETs) originate from the neuroendocrine cell system in the bronchial and gastrointestinal tract and can produce hormones leading to distinct clinical syndromes. Systemic treatment of patients with unresectable NETs aims to control symptoms related to hormonal overproduction and tumor growth. In the last decades prognosis has improved as a result of increased detection of early stage disease and the introduction of somatostatin analogs (SSAs) as well as several new therapeutic options. SS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 219 publications
(292 reference statements)
0
57
0
Order By: Relevance
“…First, the in vitro activity of OCT was tested in BON-1 cells, which express SST 1 , SST 2 , and SST 5 : OCT inhibited cAMP accumulation, CgA secretion, and MAP kinase activity [164], Akt-phosphorylation and cell growth [36], and tumor growth [165]. On the contrary, other studies reported the lack of significant anti-proliferative effects in both BON-1 and QG-1 cells [166,167] neither in 2D cultures nor in 3D-spheroid models [168], as well as in mice bearing BON-1 xenografts [166]. The BON-1 cell line has been also proposed as a model mimicking the IGF system on GEP-NETs and a model used to test the activation of IGF-related factors upon treatment with OCT and PAS [169].…”
Section: Comparison Between First- and Second−generation Somatostamentioning
confidence: 99%
“…First, the in vitro activity of OCT was tested in BON-1 cells, which express SST 1 , SST 2 , and SST 5 : OCT inhibited cAMP accumulation, CgA secretion, and MAP kinase activity [164], Akt-phosphorylation and cell growth [36], and tumor growth [165]. On the contrary, other studies reported the lack of significant anti-proliferative effects in both BON-1 and QG-1 cells [166,167] neither in 2D cultures nor in 3D-spheroid models [168], as well as in mice bearing BON-1 xenografts [166]. The BON-1 cell line has been also proposed as a model mimicking the IGF system on GEP-NETs and a model used to test the activation of IGF-related factors upon treatment with OCT and PAS [169].…”
Section: Comparison Between First- and Second−generation Somatostamentioning
confidence: 99%
“…Nutrition care plans are an integral part of the multidisciplinary management of patients with NETs. Nutritionists with expertise in NETs can provide dietary approaches to improve the quality of life and nutritional status during therapeutic modalities used for patients with NETs and particular in palliative care [73]. Unfortunately, there are not enough registered physicians and dieticians who have expertise in the nutritional management of NETs [74].…”
Section: Dietary Recommendations For Nen Patientsmentioning
confidence: 99%
“…Factors such as unhealthy diets, tobacco, alcoholism, infections and occupational exposures contribute to the formation of neoplasms [75]. The need for consistent dietary guidelines for NEN patients and collaboration with nutritionists in multidisciplinary healthcare teams in NET management have been emphasized by other authors [69][70][71][72][73][74][75][76]. Recommendations for a healthy diet are based on the 2015-2020 Dietary Guidelines Advisory Committee for patients with newly diagnosed asymptomatic NETs [77].…”
Section: Dietary Recommendations For Nen Patientsmentioning
confidence: 99%
“…For years, somatostatin analogues such as octreotide and lanreotide formed the mainstay of siteagnostic adjuvant therapy for advanced NETs. 101 Peptide receptor radionuclide therapy has recently been shown to improve PFS and OS in metastatic midgut NETs. 102,103 Specifically, 177 Lu-Dotatate particles are injected into the patient, with the Dotatate component having an affinity for somatostatin receptors on the tumours and the 177 Lu isotope delivering cytotoxic radiation.…”
Section: Gastrointestinal Neuroendocrine Neoplasmsmentioning
confidence: 99%
“…Other targeted therapies under investigation for NETs include everolimus and sunitinib. 101,106 NETs should not be confused with poorly differentiated neuroendocrine carcinomas, which are rare, aggressive and primarily treated with platinum-based chemotherapy, 107 although sunitinib may also have some efficacy. 108 The selective transcription inhibitor lurbinectedin recently received US FDA approval for second-line treatment of metastatic small cell lung carcinoma based on encouraging results from a Phase II trial.…”
Section: Gastrointestinal Neuroendocrine Neoplasmsmentioning
confidence: 99%